Meso-scale Study of Bond Behavior between Ribbed Steel Rebar and Fiber-reinforced Cementitious Composite Considering Rebar Rib Geometry - Akbarifar, Reza; Mortezaei, Alireza; Babaei, Ali (Periodica Polytechnica Civil Engineering, 2024)
This study aims to develop a meso-scale finite element approach to investigate the pull-out behavior of ribbed steel rebar and fiber-reinforced cement composites. We considered separately the three phases of steel fibers, cement composite matrix, and rebar within the meso-scale finite element model. A random distribution of fibers was generated in the matrix based on the geometric characteristics of the fibers and their volume fraction. By employing the interfacial transition zone (ITZ) model, the interaction between rebar and fibers with cement composite was simulated. Experimental pull-out tests were conducted to determine the parameters of the model. A meso-scale finite element model was validated and the effect of rebar diameter and fiber volume fraction on the bond behavior of rebar with fiber-reinforced cement composites was examined. In accordance with the experimental results, the bond-slip curve obtained with the meso-scale finite element model can be divided into five areas: non-slip, slight slip, splitting, decreasing, and residual. Additionally, it can be observed that fiber-free cement composites fail by splitting, whereas specimens containing fibers fail by sliding. This numerical model is therefore able to predict and estimate the influence of a variety of parameters on the pull-out response between fiber-reinforced cement composite and ribbed bar and failure mechanisms without the need for expensive and time-consuming testing.